Multifunctional reduced graphene oxide/carbon nanotubes/epoxy resin nanocomposites based on carbon nanohybrid preform. Issue 1 (2nd January 2020) - Wang, Baichen; Dou, Shuo; Li, Wei; Gao, Yu
ABSTRACT: Constructing continuous carbon network in insulative polymer matrix is of great significance for carbon nanocomposites to be used in a huge range of applications. In this study, multifunctional reduced graphene oxide (RGO)/carbon nanotubes (CNTs)/epoxy resin (EP) nanocomposites based on carbon nanohybrid preform is prepared via vacuum-assisted infiltration route. The roles of CNTs and 2-ethyl-4-methylimidazole (EMI) playing in carbon nanohybrid preform, chemically and physically, are identified to elucidate the structure and properties of the RGO/CNTs/EP nanocomposites. The much better thermal stability of RGO/CNTs preform testifies that GO sheet was chemically reduced by EMI. The as-made nanocomposites were examined with respect to mechanical reinforcement, thermal and electrical conductance. The interfacial compatibility and bonding between carbon nanohybrid framework and EP are achieved, which is responsible for the increased mechanical properties at the optimized formulations of carbon nanohybrid preform. The significantly enhanced electrical and thermal conductivities of carbon nanocomposites are ascribed to the interconnected sp 2 -hybridized carbon network consisting of the isolated graphitic domains of RGO sheets and structurally intact CNTs bridges throughout the polymer bulk.